Pengaruh Brain Gym terhadap Konsentrasi Belajar Siswa Kelas IX IPA dalam Pembelajaran Matematika di SMA XYZ Tangerang [The Effects of Brain Gym in Helping Students' Concentration in Learning Math in Grade XI Science at XYZ Senior High School Tangerang] - Tica Chyquitita; Yonathan Winardi; Dylmoon Hidayat (Universitas Pelita Harapan, 2018)
Math is considered to be one of the subjects that make it difficult for students to concentrate during the learning process because their brains become tired and tense. One of the most popular and trusted ways to improve learning is by using a 'gym gym' approach. Therefore, the researchers wanted to see whether the 'gym gym' approach could improve learning concentration. The research used a quasi-experimental post-test only control group design. The population was the students of class XI Science Basic General Math A and B, while the sample was 15 students from XI Science B as the experimental group. Using the Mann-Whitney U-test with an alpha level of 0.05 indicated the asymptote Sig of 0.001 <0.05. This means that the concentration of learning in the experimental group was lower than that of the control group so it is concluded that the ‘brain gym’ approach did not significantly affect students’ concentrationBAHASA INDONESIA ABSTRAK: Matematika menjadi salah satu pelajaran sulit yang menyebabkan siswa susah untuk berkonsentrasi selama belajar karena otak menjadi lelah dan tegang. Salah satu cara yang populer dan dipercaya dapat meningkatkan konsentrasi belajar adalah brain gym. Sehingga peneliti ingin melihat apakah terdapat pengaruh brain gym terhadap konsentrasi belajar siswa. Penelitian ini menggunakan kuasi eksperimen desain post-test only control group. Populasi penelitian ini adalah kelas XI IPA A dan B dengan sampel 15 siswa dari kelas XI IPA B sebagai kelompok kontrol dan 15 siswa dari kelas XI IPA A sebagai kelompok eksperimen. Dengan menggunakan Mann-Whitney U-test dengan tingkat alfa 0,05 menunjukkan asymp. Sig sebesar 0,001<0,05. Hal ini berarti konsentrasi belajar pada kelompok eksperimen lebih rendah dari pada kelompok kontrol sehingga disimpulkan bahwa brain gym tidak berpengaruh terhadap konsentrasi belajar siswa.